On behaviour of integral functions represented by the Dirichlet series on the real axis - Vinnitsky , В. V.; Sorokivsky , V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
Conditions are found under which for an entire function $f$  represented by a Dirichlet series with finite Ritt order on some sequence $(x_k), 0